2021
DOI: 10.3389/fphar.2021.727528
|View full text |Cite
|
Sign up to set email alerts
|

Polypodium vulgare L. (Polypodiaceae) as a Source of Bioactive Compounds: Polyphenolic Profile, Cytotoxicity and Cytoprotective Properties in Different Cell Lines

Abstract: Pteridophytes, represented by ferns and allies, are an important phytogenetic bridge between lower and higher plants. Ferns have evolved independently of any other species in the plant kingdom being its secondary metabolism a reservoir of phytochemicals characteristic of this taxon. The study of the potential uses of Polypodium vulgare L. (Polypodiaceae) as medicinal plant has increased in recent years particularly when in 2008 the European Medicines Agency published a monograph about the rhizome of this speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 77 publications
0
20
0
1
Order By: Relevance
“…Despite the low number of studies on ferns, the methanolic extract of their fronds is considered plant parts with a high amount of antioxidant phytochemicals ( 61 , 62 ). Currently, the extracts of Polypodiaceae ferns such as Polypodium leucotomos (aqueous extract) and Polypodium vulgare L. (methanolic extract) have been reported as antioxidant and cytoprotective agents in vitro ( 63 , 64 ). However, few ferns of the Aspleniaceae family, despite being the main ferns in Europe, have been studied as plant matrices for the contribution of antioxidant phytochemicals ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low number of studies on ferns, the methanolic extract of their fronds is considered plant parts with a high amount of antioxidant phytochemicals ( 61 , 62 ). Currently, the extracts of Polypodiaceae ferns such as Polypodium leucotomos (aqueous extract) and Polypodium vulgare L. (methanolic extract) have been reported as antioxidant and cytoprotective agents in vitro ( 63 , 64 ). However, few ferns of the Aspleniaceae family, despite being the main ferns in Europe, have been studied as plant matrices for the contribution of antioxidant phytochemicals ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In traditional Polish medicine, polypody fern rhizome infusions were used as an expectorant and diuretic and were used exclusively for treating chronic nephritis and pyelonephritis [21,22]. P. vulgare is very rich in biologically active compounds, which belong to different classes of plant metabolites: saponins, triterpenoids, ecdysteroids, tannins, flavonoids, and phenolics [20,29,30,32,33]. UHPLC-MS analysis of PvE that was used in our study revealed the presence mainly of osladin and polypodoside A belonging to saponins, flavonoids: catechin derivatives and afzelechin, and ecdysteroid hormones: hydroxyecdysone and polypodine B.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant is currently any chemical that prevents, slows, or reverses oxidative damage in the target molecule [ 81 ]. It is widely known that flavonoids have a higher antioxidant capacity due to their capacity to scavenge free radicals [ 81 ].…”
Section: Literature Review Based On Research Questionsmentioning
confidence: 99%
“…The antioxidant is currently any chemical that prevents, slows, or reverses oxidative damage in the target molecule [ 81 ]. It is widely known that flavonoids have a higher antioxidant capacity due to their capacity to scavenge free radicals [ 81 ]. Flavonoids are direct scavengers of ROS and RNS downregulation of radical-producing ones and upregulation of ROS-removing enzymes, hence acting as strong antioxidants.…”
Section: Literature Review Based On Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation